2023
DOI: 10.3390/molecules28135217
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Interactive and Damage Study with meso-Tetra(2-thienyl)porphyrins Coordinated with Polypyridyl Pd(II) and Pt(II) Complexes

Bernardo Almeida Iglesias,
Níckolas Pippi Peranzoni,
Sophia Iwersen Faria
et al.

Abstract: We report the DNA-binding properties of three porphyrins with peripheral thienyl substituents (TThPor, PdTThPor and PtTThPor). The binding capacity of each porphyrin with DNA was determined by UV-Vis and steady-state fluorescence emission spectroscopy combined with molecular docking calculations. The results suggest that the interaction of these compounds probably occurs via secondary interactions via external grooves (minor grooves) around the DNA macromolecule. Moreover, porphyrins containing peripheral Pd(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…23 It is known that intercalation results in DNA elongation, due to the separation of base pairs at the intercalation site, which at the same time leads to an increase in the relative specific viscosity of such solutions. 24 The results of viscosity measurements of complexes C1–C4 were indicated that complexes are not performing intercalation between the DNA bases, and which probably bind to minor/major grooves. The obtained measurement values were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…23 It is known that intercalation results in DNA elongation, due to the separation of base pairs at the intercalation site, which at the same time leads to an increase in the relative specific viscosity of such solutions. 24 The results of viscosity measurements of complexes C1–C4 were indicated that complexes are not performing intercalation between the DNA bases, and which probably bind to minor/major grooves. The obtained measurement values were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of other structural techniques, viscosity measurements are considered as one of the most unambiguous methods to determine intercalation or non-intercalation binding of small compounds with the nucleobases of DNA. 70 The results of viscosity measurements are shown in Fig. 6.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%